Angiostatic activity of the antitumor cytokine interleukin-21 - Castermans, Karolien (Blood, 2008)
Interleukin-21 (IL-21) is a recently described immunoregulatory cytokine. It has been identified as a very potent immunotherapeutic agent in several cancer types in animal models, and clinical studies are ongoing. IL-21 belongs to the type I cytokine family of which other members, ie, IL-2, IL-15, and IL-4, have been shown to exert activities on vascular endothelial cells (ECs). We hypothesized that IL-21, in addition to inducing the antitumor immune response, also inhibits tumor angiogenesis. In vitro experiments showed a decrease of proliferation and sprouting of activated ECs after IL-21 treatment. We found that the IL-21 receptor is expressed on vascular ECs. Furthermore, in vivo studies in the chorioallantoic membrane of the chick embryo and in mouse tumors demonstrated that IL-21 treatment disturbs vessel architecture and negatively affects vessel outgrowth. Our results also confirm the earlier suggested angiostatic potential of IL-2 in vitro and in vivo. The angiostatic effect of IL-21 is confirmed by the decrease in expression of angiogenesis-related genes. Interestingly, IL-21 treatment of ECs leads to a decrease of Stat3 phosphorylation. Our research shows that IL-21 is a very powerful antitumor compound that combines the induction of an effective antitumor immune response with inhibition of tumor angiogenesis.